Examining the Role of Liquefiable Layer Thickness and Depth on the Seismic Lateral Response of Piles through Numerical Analyses - Ari, Abdulmuttalip; Demir, Selcuk; Ozener, Pelin (ASCE-AMER SOC CIVIL ENGINEERS, 2023)
In nature, soil layers possess large variability during their geological process. This variability may also lead to differences in the location and thickness of nonliquefiable and liquefiable soil layers. In practice, the impact of liquefaction on the pile can be ignored at depths greater than 20 m due to high confining stress levels and a lack of liquefaction triggering data. On the other hand, this approach may underestimate design loads in many cases, especially in deep-seated and embedded engineering structures. This paper presents the bending response of piles installed through liquefiable layers located at depths beyond 20 m, and parametric analysis was conducted for a wide range of liquefiable layer thicknesses and depths by using OpenSeesPL (version 3.0.2) software. The numerical results were evaluated considering the inelastic concrete pile behavior under different earthquake records and different peak ground accelerations. The findings show that liquefaction can lead to a failure of piles even at depths greater than 20 m, and thus, a design consideration of piles may require a more comprehensive view considering the liquefiable layer depth and thickness effect.
Keywords: Liquefaction; Pile; Numerical analysis; OpenSeesPL; Deep liquefiable layer; CYCLIC MOBILITY; CENTRIFUGE; SOIL; BEHAVIOR; FAILURE; MODEL; FOUNDATIONS; SIMULATION; DAMAGE; Engineering